Analyzing Of Levels Of Job Satisfaction Of Volleyball Classification Referees In The Terms Of Some Parameters, - Karataş, Ö., Gündoğdu, C., Yücel, A. S., Hacıcaferoğlu, S., Karadağ, T. F., Hacıcaferoğlu, B., (My University, 2012)
This research was carried out in order to determine the levels of job satisfaction of volleyball classification referees in the terms of some parameters (gender, age, marital status, duration of refereeing). The referees carrying out a duty in the Turkey leagues of 2011-2012 seasons constitute the nature of the research. At the same time, 136 classification referees who were selected randomly between 440 classification referees depend on the Volleyball Federation of Turkey constitute its sample. SPSS packaged software was used for the statistical analysis. Measurement tool consists of two parts. The evaluation was carried out intended for determine the demographic characteristics of the referees in the first section, "Minnesota Job Satisfaction Scale" was used in the second section. Validity and reliability studies were carried out and reliability co-efficient (cronbach alpha) was found as 0.75. Determined that there is no difference statistically between levels of the job satisfaction of the referees according to their genders, also there is significant difference statistically between levels of the intrinsic job satisfaction of the referees according to their ages, marital status and duration of the refereeing. As a result, it is concluded that as age goes by, job satisfaction is increasing in the parallel of this, increasing of the experience and authority depending on the duration of refereeing, integration of reward and referees works are effective in the emergence of this difference.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Volleyball; Referee; Job Satisfaction; Variable; Classification